Zwitterionic surfactants in ion binding and catalysis. (November 2017) - Gerola, Adriana P.; Costa, Paulo F.A.; Quina, Frank H.; Fiedler, Haidi D.; Nome, Faruk
Abstract: Zwitterionic surfactants have unique properties for applications in separation methods and catalysis. Their properties and efficiencies depend on two main factors: surfactant structure and preferential interactions of zwitterionic surfactant interfaces with anions. Structural changes are related to hydrocarbon chain length, distance between charges, and type and order of functional groups in the polar head. Interactions of anions with zwitterionic micelles follow the Hofmeister series and change the surface charge. The interactions between surfactants and molecules/ions allow the rational control of separation by chromatography and micellar capillary electrophoresis; cloud point extraction; and stabilization and catalytic activity of biomolecules and nanoparticles. Graphical abstract: